Inflammatory cell infiltration and resolution of kidney inflammation is orchestrated by the cold-shock protein Y-box binding protein-1 - Bernhardt, Anja; Weng, Honglei (Kidney international, 2017)
Tubular cells recruit monocytic cells in inflammatory tubulointerstitial kidney diseases. The cell-cell communication that establishes pro- or anti-inflammatory activities is mainly influenced by cytokines, reactive oxygen species, nitric oxide, and phagocytosis. Key proteins orchestrating these processes such as cold-shock proteins linked with chemoattraction and cell maturation have been identified. The prototypic member of the cold-shock protein family, Y-box binding protein (YB)-1, governs specific phenotypic alterations in monocytic cells and was explored in the present study. Following tubulointerstitial injury by unilateral ureteral obstruction, increased inflammatory cell infiltration and tubular cell CCL5 expression was found in conditional Ybx1 knockout animals with specific depletion in monocytes/macrophages (YB-1ΔLysM). Furthermore, YB-1ΔLysM mice exhibit enhanced tissue damage, myofibroblast activation, and fibrosis. To investigate relevant molecular mechanism(s), we utilized bone marrow-derived macrophage cultures and found that YB-1-deficient macrophages display defects in cell polarization and function, including reduced proliferation and nitric oxide production, loss of phagocytic activity, and failure to upregulate IL-10 and CCL5 expression in response to inflammatory stimuli. Co-culture with primary tubular cells confirmed these findings. Thus, monocytic YB-1 has prominent and distinct roles for cellular feed-forward crosstalk and resolution of inflammatory processes by its ability to regulate cell differentiation and cytokine/chemokine synthesis.